2011
DOI: 10.1017/s0144686x11000729
|View full text |Cite
|
Sign up to set email alerts
|

Help from spouse and from children among older people with functional limitations: comparison of England and Finland

Abstract: Future increases in need of old-age care warrant research on receipt of informal care among older people in different policy and cultural contexts. Separating informal care into help provided by spouse and by children may shed more light on dynamics of informal help, important in alleviating the demands on the formal sector. Using nationally representative data from England and Finland, we performed logistic regression analyses to study receipt of help from spouse and children among community-dwelling persons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Moreover, the source of care supportformal services or informal helperswith whom spousal care-giving is shared or to whom care is outsourced might vary, too, with socioeconomic status. Care receivers with a higher socio-economic status have been shown to be less dependent on informal care (Arber and Ginn, 1992;Blomgren et al, 2011), as they are more likely to be able to pay for formal care services. In many European countries, even the publicly provided formal care partly needs to be paid 'out of pocket' by the care receiver or the number of care hours guaranteed are not sufficient for covering the care need.…”
Section: Economic Explanations For Care-givingmentioning
confidence: 99%
“…Moreover, the source of care supportformal services or informal helperswith whom spousal care-giving is shared or to whom care is outsourced might vary, too, with socioeconomic status. Care receivers with a higher socio-economic status have been shown to be less dependent on informal care (Arber and Ginn, 1992;Blomgren et al, 2011), as they are more likely to be able to pay for formal care services. In many European countries, even the publicly provided formal care partly needs to be paid 'out of pocket' by the care receiver or the number of care hours guaranteed are not sufficient for covering the care need.…”
Section: Economic Explanations For Care-givingmentioning
confidence: 99%
“…Shanas 1979). Consistent with this reasoning, Ha et al (2006) found that older persons’ dependency on their adult children grows with widowhood and Blomgren et al (2012), among others, have shown that ageing parents living with a spouse are markedly less likely to receive support from their adult children than their counterparts not living with a spouse (cf. Jacobs et al 2016; Van den Broek et al 2017).…”
Section: Introductionmentioning
confidence: 88%
“…Children may respond to parental health limitations by taking on support tasks (Blomgren et al 2012; Silverstein et al 2006; Van den Broek and Dykstra 2017). Although providing informal care can be rewarding (Cohen et al 2002; Habermann et al 2013), it can also be demanding and time consuming (Attias-Donfut 2001; Habermann et al 2013).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Several parent characteristics were included because they are known predictors of intergenerational care (Blomgren et al 2012; Brandt, Haberkern and Szydlik 2009; Haberkern and Szydlik 2010; Ogg and Renaut 2006). We included a dummy variable to distinguish mothers from fathers, as well as measures for the impaired parent's age and number of children.…”
Section: Methodsmentioning
confidence: 99%
“…As described earlier, Pickard (2012) and Ulmanen and Szebehely (2015) have suggested that the negative association between the availability of residential care and the provision of care to community-dwelling older individuals by their adult children may in part be mediated by the prevalence of severe care needs among community-dwelling individuals. It is well-established that adult children are more likely to provide care to parents when the latter's care needs are more severe (Blomgren et al 2012; Brandt, Haberkern and Szydlik 2009; Haberkern and Szydlik 2010; Ogg and Renaut 2006; Vlachantoni et al 2015). When beds in residential care settings are relatively widely available, particularly older adults with severe needs will more often be admitted to residential care settings, and thus be selected out of the community ( cf.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%